Correlates of Attempts to Quit Smoking: A Hierarchical Multiple Linear Regression Analysis - Siddiq, Muhammad; Rahman, Md Mizanur; Gahamat, Mohd Faiz (IIUM Medical Journal Malaysia, 2021)
Background: Smoking is a public health concern that contributes to non-communicable disease fatalities. Nearly five million Malaysians aged 15 years and above are estimated to be smokers. Quitting smoking is complicated and challenging for most smokers to attempt and succeed. Not everyone enjoys it, but some have decided and/or tried to stop smoking completely. This study aimed at identifying predictors of quit smoking attempts. Methods: The researchers designed a cross-sectional study conducted in Samarahan Division, Sarawak, Malaysia. Data from 777 smokers were collected via face-to-face interview using a validated structured questionnaire. A hierarchical multiple regression analysis was performed to determine the factors associated with quit smoking attempts by IBM SPSS version 22.0. A p-value of ≤.05 was considered statistically significant. Results: The average age of the smokers was 43.46 years old, with the male to female ratio of 8.96:1. The median age of starting and being regular smoking were 20 and 23 years, respectively. The hierarchical multiple linear regression analysis revealed that motivation (β=.220, p<.001), intention to quit (β=.148, p><.001), age at regular smoking (β=.131, p><.01), gender (β=.088, p><.01) appeared to be significant predictors of quit smoking attempt. Self-efficacy (β=-.101, p><.05) had a negative effect on quit smoking. However, nicotine dependency and the age of respondents did not affect smoking cessation. Conclusion: Smoking cessation motivation, intention, and age of regular smokers were associated with quit attempts.Conclusion: Smoking cessation motivation, intention, and age of regular smokers were associated with quit attempts. Therefore, the aim of a future campaign should be to reinforce motivation, increase the level of intention and self-esteem for successful smoking cessation.